2023
DOI: 10.1021/acsbiomaterials.3c01173
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1-Expressing Extracellular Vesicles for the Treatment of Pneumonia

Yi Wu,
Heng Wang,
Anning Song
et al.

Abstract: Acute respiratory distress syndrome (ARDS) is a severe lung condition with a high mortality rate and a lack of effective drug therapy. In this work, we developed mesenchymal stem cell (MSC)-derived extracellular vesicles with high PD-L1 expression (MSC-EVs-PD-L1) for treating lipopolysaccharide (LPS)-induced pneumonia by intratracheal administration. We found an upregulation of PD-1 expression in the inflammatory region of murine lungs; hence, MSC-EVs-PD-L1 exerted immunosuppressive effects via the PD-1/PD-L1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Wu et al. have shown that PD-L1 overexpressing MSC-EVs have enhanced therapeutic activity compared to native EVs in a model of LPS-induced pneumonia in mice ( 77 ). Other teams also used PD-L1 overexpressing MSC-EVs, showing an increased therapeutic activity in their in vitro and in vivo models.…”
Section: The Immunomodulatory Bioactive Molecules Of Msc-derived Secr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al. have shown that PD-L1 overexpressing MSC-EVs have enhanced therapeutic activity compared to native EVs in a model of LPS-induced pneumonia in mice ( 77 ). Other teams also used PD-L1 overexpressing MSC-EVs, showing an increased therapeutic activity in their in vitro and in vivo models.…”
Section: The Immunomodulatory Bioactive Molecules Of Msc-derived Secr...mentioning
confidence: 99%
“…Genetic modifications of MSC producing EVs can improve the immunomodulatory potential of MSC-EVs. A few studies already described above have targeted specific immunomodulatory proteins such as IDO ( 100 ), IL-10 ( 44 ), TSG-6 ( 52 ), TGF-β, PTX3, miR-let7-5p and miR-21-5p ( 25 ), CD73 ( 66 ), PD-L1 ( 77 79 ), in order to secrete more of these specific proteins and induce a better immunoregulatory activity of MSC-EVs. Genetic modifications can also target the expression of bioactive miRNAs.…”
Section: Msc Priming For Enhanced Immunomodulatory Potentialmentioning
confidence: 99%